A Two-Year Radiostereometric Follow-up of the First Generation Birmingham Mid Head Resection Arthroplasty. Issue 4 (July 2014) - Itayem, Raed; Arndt, Anton; Daniel, Joseph; McMinn, Derek J.W.; Lundberg, Arne
During the first decade of the 21st century, metal-on-metal hip resurfacing became one of the main treatment options for younger, more active patients with osteoarthritis. However, as a result of the reported failure rate of both total hip replacement (THR) and resurfacing in patients with considerable loss of bone stock in the femoral head (e.g. in extensive avascular necrosis), other solutions have been sought for these patients. The short-stemmed Birmingham Mid Head Resection prosthesis (BMHR) combines a metal-on-metal articulation and a femoral neck preserving feature. In this study, radiostereometric analysis (RSA) was used to study migration of the BMHR femoral component in 13 hips. Translations and rotations were measured up to two years. Relative values showed no statistically significant migration. Absolute values demonstrated settling in occurring between zero and two months postoperatively in all directions studied. From two months to two years no significant migration occurred except for rotation around the x-axis of the femoral segment (p = 0.049). After initial settling-in, absolute values were low, indicating that there was no evidence of early migration or loosening of the components.